Mohamedou Ould Slahi's Guantánamo Diary and Prison Writing from Africa. (June 2020) - Roux, Daniel
Abstract : If the unvarnished power of the state has a face, then it is the prison. When the mask of cultural hegemony slips, we encounter the walls of the penal institution, its barbed wire, and its blankly functional architecture, mute and unseeing. A prison is one of the most concentrated modalities of state power. By definition, a prison is a zone of exclusion; it defines the normal, everyday civic sphere by defining a site of exception. A prison has its own distinctive logic and temporality, in Ngũgĩ wa Thiong'o's words, "dull, mundane, monotonous, tortuous in its intended animal rhythm of eating, defecating, sleeping, eating, defecating, sleeping" (1981:116). It is a world of boredom, isolation, and fear. Nonetheless, because of its close proximity to state power, the prison also offers a sharp-edged reflection of the operation of power in a society. As Michael Hardt observes, "Those who are free, outside of prison looking in, might imagine their own freedom defined and reinforced in opposition to prison time. When you get close to prison, however, you realize that it is not really a site of exclusion, separate from society, but rather a focal point, the site of the highest concentration of a logic of power that is generally diffused throughout the world" (1997:66). Or as Robben Island prisoner Michael Dingake remarked in his 1987 autobiography, "Prison is the heart of oppression in any oppressive society" (1987:228).